Keefektifan Model Problem Based Learning (PBL) Berbasis Etnomatematika Terhadap Hasil Belajar Siswa Materi Keliling Bangun Datar Kelas IV SDN Pedurungan Lor 01 Semarang - Ana Fitria; M Yusuf Setia Wardana; Mei Fita Arsi Untari (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study is to improve student learning outcomes of class IV circumferential shapes using Ethnomathematic Based PBL models. This study used a quantitative method with a True Experimental Design in the form of a pretest-posttest Control Group Design. The data analysis technique used the t-test on the posttest value. With learning outcomes that are supported by static calculations after the mathematics learning process that improves student learning outcomes with the Ethnomathematic based PBL model in the experimental class and mathematics learning has a slight increase in the control class. It can be seen that the final conditions of student learning outcomes vary. Through the t-polled variant test, it proves that the t-count is 2.566> t-table 2.021 then h0 is rejected and Ha is accepted, meaning that it can be said that the Effectiveness of the Ethnomatic Based PBL Model on Student Learning Outcomes of Class IV Circular Building Materials at SDN Pedurungan Lor 01 Semarang.